Cloud-based process design in a digital twin framework with integrated and coupled technology models for blisk milling - Rudel, Viktor; Kienast, Pascal; Vinogradov, Georg; Ganser, Philipp; Bergs, Thomas (Frontiers in Manufacturing Technology, 2022)
In this publication, the application of an implemented Digital Twin (DT) framework is presented by orchestration of CAM-integrated and containerized technology models carrying out FEM-coupled simulations for the finishing process of a simplified blade integrated disk (blisk) demonstrator. As a case study, the continuous acquisition, processing and usage of virtual process planning and simula-tion data as well as real machine and sensor data along the value chain is presented. The use case demonstrates the successful application of the underlying DT framework implementation for the pre-diction of the continuously changing dynamic behavior of the workpiece and according stable spindle speeds in the process planning phase as well as their validation in the actual manufacturing phase.